Novel modifications in a conventional clinker making process for sustainable cement production. (1st June 2019) - Benhelal, Emad; Shamsaei, Ezzatollah; Rashid, Muhammad Imran
Abstract: The current investigation proposes modifications in a clinker making process to separate calcination reaction from fuel combustion in the calciner, resulting in pure carbon dioxide production. Very hot stream of pure carbon dioxide or a mixture of carbon dioxide and steam is used as the heat carrier to supply required energy for endothermic calcination reaction. The proposed designs which internally separate 90 wt% carbon dioxide from limestone decomposition are environmentally and economically compared to the integration of a clinker making and a MEA carbon dioxide capture process as the conventional scenario. Results show that the proposed modifications significantly reduced carbon dioxide emissions, energy consumption and the cost of carbon dioxide capture in clinker making process. Highlights: 74.5 t-CO2 /h was internally captured in new designs. New designs reduced total CO2 emissions from 184.6 to 79 and 43.1 t-CO2 /h. New designs reduced the cost of CO2 capture from $U.S 59.6 to 32.9 and $U.S 22.1. One of the main challenges of the proposed designs is the high capital cost.